Decarbonisation challenges for steelmaking and scrap recycling role - Stovpchenko , G.P.; Medovar , L.B. (Theory and Practice of Metallurgy, 2025)
This article discusses the challenges the steelmaking industry faces in striving to achieve competitive alternatives and potential solutions in response to the imperatives of decarbonization and zero-waste manufacturing. Expanding scrap recycling is a logical practical solution that the steel industry must pursue to effectively reduce its carbon emissions amidst its current structure. One of the steps towards achieving this is by utilizing alternative scrap sources to enhance iron recovery. The Recovery Slagged Scrap (RSS) from steelmaking includes metal pieces covered by low-conductive slag, which changes its melting behaviour. Analysis of trials results has shown that adding RSS to BOF iron-bearing charge mix can speed up the formation of primary slag and at proper consumption does not pose technological difficulties. Utilizing RSS as a coolant or slag-forming addition may improve the melting process and provide cost reduction of a charge mix for a steelmaking facility.